Analysis of Growth Strategy at Wuling Motors Makassar As A Response to Facing Economic Globalization Challenges - Dafitri Anggika; Asty Almaida; Abdul Rahman Kadir (Green Publisher Indonesia, 2024)
Growth Strategy Analysis at the Wuling Motors Kumala Makassar Company as a Response to Facing the Challenges of Economic Globalization, is a research to get an overview of the company's internal strengths, market opportunities, company potential based on internal and external factors, as well appropriate growth strategies for carried out in operating the company. The aim of this research is to determine the company's response to facing the challenges of economic globalization that occur in Indonesia, especially in the automotive market segment in the marketing area of South Sulawesi, and Indonesia in general. This research method uses a qualitative approach, where the theoretical basis used refers to the opinions of several experts, in the form of books, journals, articles and other scientific writings related to this research. The data analysis used in this research is SWOT analysis (Rangkuti, Freddy. 2006.